Non-governmental organizations’ motivation to diversify: self-interest or operation-related? Evidence from Uganda - Dang, Canh Thien; Owens, Trudy (Oxford University Press, 2024)
Abstract Understanding the mechanisms that guide non-governmental organizations’ (NGOs) managerial decisions is a key to effective development policies. One fundamentally strategic decision is the number of activities an NGO offers. We provide a conceptual framework based on the agency theory to study the motivations underlying strategic decisions of development NGOs in Uganda. We test whether diversifying into many activities is driven by operational reasons or by personal gains of NGO managers. Following a historic flood in 2007, NGOs that rely more on contractual income offer fewer activities than their counterparts in less affected areas. The results support theoretical explanations that operational motives such as risk-reduction or cost complementarity dominate personal and for-profit-like motives. Our article contributes to the debates around the ethical and governmental foundation of the non-profit sector, highlighting the different roles of personal and operational aspects in the decisionmaking process
Keywords: non-governmental organizations’ (NGOs; NGOs in Uganda; ethical and governmental foundation of the non-profit sector